Implementasi Teknologi Monitoring Kualitas Tambak Berbasis Iot Bagi Petani Tambak Sinar Bonto Manai, Pangkep - Muh. Iswal Burhan; Hilda Ashari; Aulia Rahmah; Muh. Riska; Sari, Dessy Ana Laila (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
Traditional milkfish pond management by the Sinar Bonto Manai Farmer Group in Pangkep Regency faces two main problems: difficulties in accurately monitoring water quality and limited electricity access, which hinders technology adoption. This community service program aimed to address these issues through the implementation of appropriate technology. The implementation method was designed participatively in four stages: (1) preparation and capacity building through training and seminars, (2) implementation of an Internet of Things (IoT)-based water quality monitoring system integrated with a Solar Power Plant (PLTS), (3) mentoring on data utilization, and (4) evaluation. The results showed 100% partner participation with a significant increase in knowledge, with overall understanding rising from 33% in the pre-test to 95% in the post-test. The IoT-PLTS monitoring system, accessible via a smartphone application, was successfully installed and operated properly. Final evaluation revealed not only high partner satisfaction with the system’s functionality but also tangible improvements in pond productivity, including reduced risk of failure and more stable harvest outcomes. The main achievement of this program is the successful adoption of technology that transformed farmer’s work patterns from traditional intuition-based practices to proactive, data-driven management, thereby enhancing resilience and economic potential in milkfish aquaculture.